Jessner’s Lymphocytic Infiltration of the Skin (JLIS): A Rare Forehead Skin Involvement (GAIMS Journal of Medical Sciences, 2023)
Rare cutaneous condition of Jessner’s lymphocytic infiltration of the skin (JLIS) is a chronic, benign T-cell infiltrative disorder. It is a skin disease manifesting as red-colored papules or plaques on the face, neck and back. This lesion can be single or multiple with frequent recurrence. We report the case of a 35-year-old male, who presented with on and off multiple, well defined, discrete, erythematous plaques over forehead skin with 15 years duration, exacerbated during winters. The gold standard, ‘skin biopsy’ confirmed the diagnosis of JLIS over the forehead.